Keefektifan Model Cooperative Learning Tipe Student Facilitator And Explaining Pada Mata Pelajaran Akuntansi - Siti Ma'rifah Neni Hendaryati (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2019)
The purpose of this research was to determine the effectiveness of cooperative learning model type student facilitator and explaining on accounting subjects in class XI Accounting of SMK 1 Dukuhturi. A quantitative approach with the quasi experimental design used in this research. The population is 180 students. The sampling technique used purposive cluster sampling and obtained two classes or as many as 72 students who were used as research samples. The t test is used to analyze data collected through observation, tests and documentation. The results showed that the calculation of the t test was 6.01 (tcount = 6.01).With degrees of freedom (dk) = 36 + 36 - 2 = 70, the significance level is 5% and the price is ttable = 2,000. This can be interpreted tcount > ttable , (6.01 > 2,000), so this research states that the cooperative learning model type student facilitator and explaining is effective to be used in accounting subjects in class XI Accounting of SMK 1 Dukuhturi. The effectiveness of using this model is one of the creative learning alternatives that can be applied in schools